2022
DOI: 10.5334/dsj-2022-018
|View full text |Cite
|
Sign up to set email alerts
|

Data Quality Assurance at Research Data Repositories

Abstract: This paper presents findings from a survey on the status quo of data quality assurance practices at research data repositories.The personalised online survey was conducted among repositories indexed in re3data in 2021. It covered the scope of the repository, types of data quality assessment, quality criteria, responsibilities, details of the review process, and data quality information and yielded 332 complete responses.The results demonstrate that most repositories perform data quality assurance measures, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…The aim was to understand how RDRs ensure high-quality data, and to better reflect these measures in the metadata schema. The results of the study 41 , which were based on a survey among RDR operators, show that approaches to quality assurance are diverse and depend on the mission and scope of the RDR. However, RDRs are key actors in enabling quality assurance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim was to understand how RDRs ensure high-quality data, and to better reflect these measures in the metadata schema. The results of the study 41 , which were based on a survey among RDR operators, show that approaches to quality assurance are diverse and depend on the mission and scope of the RDR. However, RDRs are key actors in enabling quality assurance.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the re3data team have also published studies reusing re3data metadata, including studies of the global state of RDR 93 , openness 39 , and quality assurance of RDRs 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Majority of the RDRs support "quality management" and granted licenses and had policies (Kim, 2018;Cho, 2019). A recent survey conducted among the RDRs indexed in re3data.org revealed that most of these repositories significantly contribute to the quality assurance of the data (Kindling and Strecker, 2022).…”
Section: About Re3datamentioning
confidence: 99%
“…The main advantage of arranging your own repository infrastructure is that you have greater control over how data are documented and presented to the public and/or researchers. Specific data repository infrastructure may also improve the data quality of the datasets [ 64 ]. However, creating and using this infrastructure leads to additional costs (especially when dealing with large quantities of data).…”
Section: Rulesmentioning
confidence: 99%